2016
DOI: 10.1111/ina.12359
|View full text |Cite
|
Sign up to set email alerts
|

Measured performance of filtration and ventilation systems for fine and ultrafine particles and ozone in an unoccupied modern California house

Abstract: This study evaluated nine ventilation and filtration systems in an unoccupied 2006 house located 250m downwind of the I-80 freeway in Sacramento, California. Systems were evaluated for reducing indoor concentrations of outdoor particles in summer and fall/winter, ozone in summer, and particles from stir-fry cooking. Air exchange rate was measured continuously. Energy use was estimated for year-round operation in California. Exhaust ventilation without enhanced filtration produced indoor PM 2.5 that was 70% low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 37 publications
0
11
0
2
Order By: Relevance
“…In addition to extending the lifetimes of unsaturated VOCs, this would reduce production of OH via ozone–alkene reactions, which is thought to be the dominant OH source indoors (except potentially in sunlit regions). Previously reported indoor ozone levels ranged from 1.6 to 50 ppbv, although most of these measurements were not made in residences (e.g., refs , , and ). A median indoor ozone level of 25 ppbv results in a dark OH production rate of ∼10 7 molecules cm –3 s –1 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to extending the lifetimes of unsaturated VOCs, this would reduce production of OH via ozone–alkene reactions, which is thought to be the dominant OH source indoors (except potentially in sunlit regions). Previously reported indoor ozone levels ranged from 1.6 to 50 ppbv, although most of these measurements were not made in residences (e.g., refs , , and ). A median indoor ozone level of 25 ppbv results in a dark OH production rate of ∼10 7 molecules cm –3 s –1 .…”
Section: Discussionmentioning
confidence: 99%
“…Table lists the number of occurrences for each mode from which UFP loss rates were estimated during the concentration decays. L represents the total rate of removal of UFPs and incorporates the additive effects of (i) deposition to indoor surfaces, (ii) deposition to AHU components (e.g., MERV 11 filter, heating/cooling coils, ducts), ,, (iii) exhaust to the outdoors via the ERV, (iv) exfiltration through the building envelope, and (v) interzonal air exchange . Thus, the apportionment of L among processes (i)–(v) was not determined.…”
Section: Methodsmentioning
confidence: 99%
“…The efficiency and the size range of PM removal varies with the MERV ratings with the smallest particles and highest removals achieved with HEPA filters and MERV 13 and greater. Unsurprisingly, studies have shown higher MERV filters are more effective at cleaning indoor air than lower MERV filters ( 28 ). The presenters recommended MERV 13 or greater filters for wildland fire smoke filtration, since these filters have some effectiveness removing the smallest particles (0.3–1.0 μm) that are most common in wildfire smoke.…”
Section: State Of Technology To Improve Indoor Airmentioning
confidence: 99%